Assessing the trade policy space to implement industrial policy in South Africa - Letsoalo, Malose Anthony (My University, 2013)
This paper undertook qualitative research to determine the trade policy space for South Africa to implement its industrial policy action plan (Ipap). The South African economy was transformed from import substitution in the 1970s to export-orientation in the 1980s. The apartheid regime failed to develop coherent policies for industrialisation. In the 1990s, there was a deliberate government decision as articulated in the GEAR policy to liberalise the economy and with regard to trade this is associated with accession to the World Trade Organisation and commitments made thereof. In 2007, the country adopted the national industrial policy framework to guide its reindustrialisation efforts and subsequently various iterations of the Ipap. Therefore, given that a lot of policy space was lost when the country joined as the WTO as a developed country, the question is “does South Africa have enough policy space to use some of the instruments that were used by successful Asian countries to industrialise”. The WTO made some of these instruments illegal. To analyse policy space, the paper looked at the effect of WTO Agreements on Subsidies and Countervailing Measures (SCM), on Trade-Related Investment Measures (TRIMS), on Government Procurement (GPA), as well as the tariff commitments. The study found that although SCM has made certain subsidies illegal, other kinds of subsidies are allowed such as those for economic development in disadvantaged regions and for rural development. Therefore, strategy and packaging of these subsidies for development is important. TRIMS was found to have significantly reduced policy space by making a number of instruments on foreign direct investment illegal such as enforcing local content as well as export requirements. Since South Africa is not party to the GPA, it retains policy space to use government procurement to promote industrialisation in the country. In terms of tariffs commitment, the study found that there is no “water” between applied and bound rate for a number of critical sectors such as textile, clothing, footwear, and furniture. However, other important sectors such as automotive and automotive components and white goods still have “water” to increase tariff in future as necessary. Therefore, the study concluded that there is policy space to implement industrial policy in South Africa but this requires strategy and closer look at the WTO rules for flexibility.
Submitted in partial fulfilment of the requirements for the degree M.Com. Development Theory and Policy in the faculty of Commerce, Law and Management at the University of the Witwayersrand, 2013
Keywords: Industrial policy; Trade agreements; WTO; World Trade Organization; South Africa